Three-dimensional reconstruction of flame temperature and H2O concentration using water vapor integrated spectral band emission. (January 2023) - Cheng, Yong; Tian, Chong; Huang, Zhifeng
Highlights: Three-dimensional gas temperature and H2 O concentration are reconstructed. Integrated gas emission in two spectral bands instead of hyperspectral data is used. Gas emission over two bands for gas temperature has advantages of two-color method. Spectral band pairs are carefully selected and the selecting criteria are presented. Abstract: Efficient and accurate reconstruction of flame temperature and species concentration is very useful for combustion monitoring. In this work, the integrated spectral band ratio (ISBR) method, which uses the ratio of two integrated spectral radiative intensities to infer temperature, is applied to reconstruct three-dimensional flame temperature and H2 O concentration distributions. First, the ratio of two integrated spectral radiative intensities is justified by gas radiation theory to only depend on gas temperature, and the influence of gas concentration and pressure on the ratio is negligible. Then, a spectral band pair is carefully selected for the measurement with an atmospheric path between the detector and the flame. In the selected spectral bands, CO2 and CO emissions are negligible compared to H2 O emission, and atmospheric absorption can be ignored. Meanwhile, gas temperature is monotonically related to the ratio of integrated spectral radiative intensities. When the uncertainty of the ratio is 2%, the error of reconstructed temperature is less than 38K with gas temperature close to 3000K, and the error decreases as the gas temperature goes down. Finally, numerical experiments on reconstruction of axisymmetric and non-axisymmetric flames are carried out. Results show that three-dimensional distributions of flame temperature and H2 O concentration can be reconstructed with high accuracy.